Respuestas

2013-10-31T13:08:51+01:00

Te voy a resolver 3 (1 - 2 y 4)
Las otras puedes trabajarlas siguiendo la misma metodologia

1 -
             5^{2} +10x = 0
            Factorizando:
            5x(x + 2) = 0
                  5x = 0               x1 = 0
                 x + 2 = 0            x2 = - 2
                                                          S = {- 2, 0}
2 -
            4x^{2} +6 = 0
            2x^{2} = -3   (dividiendo entre 2)
            x^{2} =  \sqrt{ \frac{-3}{2} }
                                     x1^{} = -  \sqrt{\frac{3}{2}} i
                                     x2^{} =  \sqrt{ \frac{3}{2}}i
                    S = { - \sqrt{\frac{3}{2}}i,  \sqrt{ \frac{3}{2} }i}
4 - 
           m^{2} + 10m + 21 = 0
          Factorizando:
                (m + 7)(m + 3) = 0
                 m + 7 = 0                   m1 = - 7
                 m + 3 = 0                   m2 = - 3
                                                                  S = {- 3, - 7}